A MOTIVAÇÃO DE PESSOAS COMO FATOR CRÍTICO PARA A GARANTIA DA QUALIDADE EM SERVIÇOS: UM ESTUDO DE CASO NUMA EMPRESA DE TECNOLOGIA DA INFORMAÇÃO - Accetta, Lúcia Teresa Alexim de Sousa (2005)
Motivation is expected to be an important vector that may or not lead to people s satisfaction. This way, enterprises can achieve great quality among their contributors. A bibliographic research was carried out and a case study was also applied in a worldwide organization in the area of Information Technology. The Theory of Motivation is emphasized on the results of the stimulus that act as strength toward people; leading them to action. The strategy of this research follows a qualitative and descriptive methodology, besides a case study. When the needs are not satisfied, it doesn t mean that the employee will remain frustrated forever. Somehow the needs will be transferred or compensated. It s shown that the Motivation Cycle is constant on people s life. The changes can be so big that affect directly the human behavior inside or outside the organization. The human aspects deserve much more attention and the motivation and satisfaction are the most important points in this process.